2015
DOI: 10.1155/2015/205054
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and ARDS: The Dark Side of Histones

Abstract: Despite advances in management over the last several decades, sepsis and acute respiratory distress syndrome (ARDS) still remain major clinical challenges and the leading causes of death for patients in intensive care units (ICUs) due to insufficient understanding of the pathophysiological mechanisms of these diseases. However, recent studies have shown that histones, also known as chromatin-basic structure proteins, could be released into the extracellular space during severe stress and physical challenges to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 100 publications
0
58
3
Order By: Relevance
“…Histones have captured attention to elucidate mechanisms of NET-induced injury (reviewed in 9799 ). Like DNA, histones are increased in the circulation during inflammatory injuries and can act as DAMPs, contributing to organ injury and death in animal models of sepsis 100102 , acute lung injury 103 , and ischemia/reperfusion (I/R) injury 104 through Toll-like receptor 104,105 or C5a receptor 103 mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Histones have captured attention to elucidate mechanisms of NET-induced injury (reviewed in 9799 ). Like DNA, histones are increased in the circulation during inflammatory injuries and can act as DAMPs, contributing to organ injury and death in animal models of sepsis 100102 , acute lung injury 103 , and ischemia/reperfusion (I/R) injury 104 through Toll-like receptor 104,105 or C5a receptor 103 mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in ECG tracings on perfused mouse hearts with histones or isolated cardiomyocytes incubated with histones we showed harmful effect of histones (Kalbitz et al, 2015). In line, other studies showed antihistone-based treatments (e.g., neutralizing antibodies, activated protein C, and heparin) to have protective effects and have significantly improved the outcomes of mice with sepsis (Xu et al, 2015). Neutralization of Cit H3 also showed survival improvement in septic mice (Li et al, 2014).…”
Section: Non-invasive Methods To Assess Heart Function In Sepsismentioning
confidence: 59%
“…Histones act as damage-associated molecular pattern molecules (DAMP) when they are released into the extracellular space (Chen et al, 2014). Extracellular histones can lead to excessive and overwhelming cell damage and death due to the high cytotoxic and proinflammatory effects, thus contributing to the pathogenesis of sepsis (Xu et al, 2015). Release of histones into the extracellular compartment has been postulated to be a major cause of death during sepsis (Chaput and Zychlinsky, 2009; Ekaney et al, 2014; Nakahara et al, 2013; Xu et al, 2009).…”
Section: Non-invasive Methods To Assess Heart Function In Sepsismentioning
confidence: 99%
“…Therapeutic approaches regarding specific attenuation of NETosis during sepsis includes: 1. Infusion of anti-citrullinated antibodies [25,38], 2. blocking platelet:PMN interactions via the peptide MKEY and anti-Mac1 antibodies [39]; 3. An interesting approach towards preventing NETosis while preserving neutrophil function is the finding of Van Avondt et al that cross-linking the signal inhibitory receptor on leukocytes-1 (SIRL-1) obviating NET release from opsonized as well as nonopsonized S. aureus [40].…”
Section: Intervention and Prognostic Opportunitiesmentioning
confidence: 99%